2006
DOI: 10.4103/0378-6323.19715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of topical 1% lindanevs5% permethrin in scabies: A randomized, double-blind study

Abstract: Permethrin (5%) cream was found to be significantly more effective in the treatment of scabies in comparison with lindane in this study, and it seems that it could be an alternative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…3) Topical GBhC 1% lotion: Earlier studies [8,[11][12][13] have reported <75% cure rate with 1% topical GBHC lotion. Nag et al, [13] have reported a cure rate of 68% only with 2% GBHC 2 applications in a day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Topical GBhC 1% lotion: Earlier studies [8,[11][12][13] have reported <75% cure rate with 1% topical GBHC lotion. Nag et al, [13] have reported a cure rate of 68% only with 2% GBHC 2 applications in a day.…”
Section: Discussionmentioning
confidence: 99%
“…2) Topical Permethrin 5% cream single application: Earliar studies [4,[8][9][10] have reported cure rate >80% with Permethrin. Higher cure rates (98%) was reported after two applications.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Permethrin 5% cream has been found to be more effective as compared to lindane and is FDA approved for the treatment of scabies. [5,6] In developing countries like India where the disease is largely prevalent in the lower socioeconomic strata, acquiring permethrin is considered an expensive option. Besides, whole body application for hours together is inconvenient and leads to poor compliance.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Similarly Hegary et al and Usha et al found permethrin to be effective as a single application with cure rate of 84.9% and 97.8% respectively. 13,5 Topical GBHC 1% lotion (single application)…”
Section: Topical Permethrin 5% Lotion (Single Application)mentioning
confidence: 99%
“…Taplin et al, Zargari M et al, Chouela et al, have found 65%, 48.9%, 44.44%, 54% cure rate respectively with 1% lindane lotion after 1 month. [10][11][12]14 Comparison of statistical significance among three groups Difference in efficacy of group I (ivermectin) therapy was statistically non-significant with group II (permethrin) but statistically significant with group III (gama benzene hexachloride). This shows that efficacy of group I therapy was comparable to group II therapy but more efficacious than group III therapy.…”
Section: Topical Permethrin 5% Lotion (Single Application)mentioning
confidence: 99%